PENGEMBANGAN E-MODUL BERBASIS VIDEO MATERI PERUBAHAN LINGKUNGAN UNTUK SISWA PADA FASE E SMA/MA - Muthia Muthia; Ade Dewi Maharani; Liza Yulia Sari (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
n the biology learning process, teachers have used various media and teaching materials such as printed books and student worksheets, supported by teaching media in the form of PowerPoint presentations. The books provided by the school library do not match the number of students, so students cannot take books home to study at home. This research aims to produce a video-based E-Module with material on environmental changes in Phase E that is valid and practical for senior high school Phase E students. This research is an R&D (Research and Development) research using a 4D model which consists of four stages, namely the definition stage, planning stage, development stage, and dissemination stage. This research was carried out to the stage of developing validation tests and practicality tests with descriptive quantitative data analysis and validation tests carried out by 1 Biology teacher, 1 material expert lecturer, 1 media expert, and 1 strategy lecturer. The practicality test will be carried out by 1 biology teacher and 30 students in Phase E senior high school. The research results showed that the validation value carried out by the validator on the e-module was very valid (90.8%), with the practicality test carried out by the Biology teacher on the e-module developed being very practical (91.6%) and by 30 people. Phase E students are very practical (84.3%). From the results of validation tests and practicality tests, it was concluded that the video-based e-module on environmental change material in Phase E senior high school was valid and practical.